The Ecology of Malaria Vectors - Charlwood, Jacques Derek (Milton : CRC Press LLC, 2019)
This practical book covers all aspects of the biology of malaria vectors, with notes on the vectors of dengue. It is the first work in this field to concentrate on mosquitoes, rather than covering all disease vectors. Authored by renowned field entomologist Jacques Derek Charlwood, it disseminates his vast experience working on mosquito biology, ecology and the evaluation of new vector control tools across five continents over the past 40 years. Covering all aspects from classification and systematics, population dynamics, vector control, to surveillance and sampling, epidemics, and a selection of case histories, the book also considers genetics and resistance, Aedes biology, and malaria and dengue models. It is designed to fill the gap between very specialized texts and undergraduate books on general disease vectors, and is ideal as a textbook for postgraduate courses in entomology and mosquito vectors of disease.
OCLC-licensed vendor bibliographic record.
Keywords: Mosquitoes as carriers of disease; Malaria; MEDICAL -- Infectious Diseases; MEDICAL -- Epidemiology; SCIENCE -- Life Sciences -- Zoology -- Entomology